X-ray line coincidence photopumping in a solar flare. Issue 3 (23rd November 2017) - Keenan, F P; Poppenhaeger, K; Mathioudakis, M; Rose, S J; Flowerdew, J; Hynes, D; Christian, D J; Nilsen, J; Johnson, W R
Abstract: Line coincidence photopumping is a process where the electrons of an atomic or molecular species are radiatively excited through the absorption of line emission from another species at a coincident wavelength. There are many instances of line coincidence photopumping in astrophysical sources at optical and ultraviolet wavelengths, with the most famous example being Bowen fluorescence (pumping of O iii 303.80 Å by He ii ), but none to our knowledge in X-rays. However, here we report on a scheme where a He-like line of Ne ix at 11.000 Å is photopumped by He-like Na x at 11.003 Å, which predicts significant intensity enhancement in the Ne ix 82.76 Å transition under physical conditions found in solar flare plasmas. A comparison of our theoretical models with published X-ray observations of a solar flare obtained during a rocket flight provides evidence for line enhancement, with the measured degree of enhancement being consistent with that expected from theory, a truly surprising result. Observations of this enhancement during flares on stars other than the Sun would provide a powerful new diagnostic tool for determining the sizes of flare loops in these distant, spatially unresolved, astronomical sources.